A method of reducing aflatoxin and ochratoxin in whole spice. - Selamat, Jinap (2011)

(untitled)
The present invention relates to a method of reducing aflatoxin and ochratoxin in whole spices characterised by the steps of applying a sulphurous salt to the whole spices to produce treated whole spices and heating the treated whole spices. The whole spices are peppercorns and the sulphorous salt is ranging from 0.25 to 2.00% w/w and selected from a group consisting of sodium bisulfite, sodium hydrosulfite and sodium sulphate. The heating is achieved by autoclaving or boiling.